The Effect of Guided Inquiry Learning on Cognitive Learning Outcomes of Elementary School Students - Rahmatullah Rahmatullah (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
Aim: This study examined the effect of the guided inquiry learning model on students' cognitive learning outcomes at the elementary school level. Method: The research employed a quasi-experimental design with a pretest–posttest control group. The participants were fourth-grade elementary school students, who were divided into an experimental group taught using the guided inquiry learning model and a control group taught using conventional instructional methods. Data on students' cognitive learning outcomes were collected through standardized achievement tests administered before and after the intervention. The obtained data were analyzed using inferential statistical techniques to determine differences between groups. Results and Discussion: The results revealed a significant difference in cognitive learning outcomes between the experimental and control groups, with students in the experimental group demonstrating higher posttest scores than those in the control group. These findings indicate that the guided inquiry learning model positively enhances students' cognitive achievement by actively engaging learners in the learning process, encouraging critical thinking, and promoting conceptual understanding. Conclusion: Based on the findings, the guided inquiry learning strategy is effective and can be implemented in elementary school classrooms as an alternative instructional approach to improve students' cognitive learning outcomes. The study also suggests that teachers should consider incorporating guided inquiry-based activities to foster more meaningful and student-centered learning experiences.